Total Diet Replacement Within an Integrated Intensive Lifestyle Intervention for Remission of Type 2 Diabetes: Lessons From DiRECT - Noronha, Jarvis C.; Thom, George; Lean, Michael E. J. (Frontiers in Endocrinology, 2022)
The prognosis for people with type 2 diabetes (T2D) remains poor, yet its seriousness is often underestimated. T2D is a manifestation, in susceptible individuals, of the disease-process of obesity, and at diagnosis, 10-year survival rates for T2D are around 50%. Here, we will examine: (a) the role of weight loss in T2D, (b) use of total diet replacements (TDRs) to induce weight loss, (c) the Diabetes Remission Clinical Trial (DiRECT) protocol and key results, (d) other dietary interventions related to T2D remission, (e) remission in real life, and (f) future directions. We conclude that remission of T2D is most likely to be achieved with a behavioural weight management programme incorporating an intensive TDR induction phase to initiate weight loss, followed by an actively supported transition onto sustainable eating patterns thereafter. Results from the DiRECT trial showed that weight loss of ≥10kg will reverse most cases of short-duration T2D, and this was achieved in a routine healthcare setting. In light of these findings, which have since been replicated in the Diabetes Intervention Accentuating Diet and Enhancing Metabolism (DIADEM-I) trial conducted in the Middle East and North Africa, it is now time to prioritise weight loss programmes for T2D remission from diagnosis.